Apakah Modal Manusia Penting untuk Mengangkat Jawa Timur dari Jebakan Kelas Menengah? - Natalia, Christiayu; Wahyudi, Setyo Tri (UI Scholars Hub, 2023)
Optimizing demographic dividend requires human capital quality improvement. However, disparities in the quality of human capital between regions in East Java becoming challenge in increasing GRDP per capita growth before demographic bonus period ends. This research analyze the effect of human capital quality on GRDP per capita growth during 2011–2022 period generally in East Java Province and specifically in districts/cities with low human capital quality. Dynamic panel data regression analysis using the First-Difference Generalized Moment Method (FD-GMM) was used in this research. The research results show a significant influence of the quality of human capital on GDP per capita growth.